2016
DOI: 10.1021/acs.orglett.5b03522
|View full text |Cite
|
Sign up to set email alerts
|

Fused Catechol Ethers from Gold(I)-Catalyzed Intramolecular Reaction of Propargyl Ethers with Acetals

Abstract: Selective gold(I)-catalyzed rearrangement of aromatic methoxypropynyl acetals leads to fused catechol ethers (1,2-dialkoxynapthalenes) in excellent yields. Furthermore, this process extends to the analogous heterocyclic and aliphatic substrates. Alkyne activation triggers nucleophilic addition of the acetal oxygen that leads to an equilibrating mixture of oxonium ions of similar stability. This mixture is "kinetically self-sorted" via a highly exothermic cyclization. Selective formation of 1,2-dialkoxy naphtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The more significant change in the σCH* population (0.08 e ) relative to the σCH population (0.03 e ) suggests that the C−H bond is a net acceptor. Interestingly, the positively charged Au center, which is commonly used as a Lewis‐acidic catalyst in organic reactions [33,34,43–52] serves as a donor in this particular situation. Again, the Au‐complex is a better donor than its Ag and Cu counterparts (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…The more significant change in the σCH* population (0.08 e ) relative to the σCH population (0.03 e ) suggests that the C−H bond is a net acceptor. Interestingly, the positively charged Au center, which is commonly used as a Lewis‐acidic catalyst in organic reactions [33,34,43–52] serves as a donor in this particular situation. Again, the Au‐complex is a better donor than its Ag and Cu counterparts (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…12 Another interesting type of cycloaromatization involves a selective gold(I)-catalyzed rearrangement of aromatic methoxypropynyl acetals, leading to fused catechol ethers. 13 Generally, the usual paradigm for applying electronic effects in organic chemistry is based on the concept that an efficient orbital overlap is required to transmit conjugation and hyperconjugation. 14 Alabugin and co-workers have provided an experimental evidence for the utility of this concept in cycloaromatization reactions involving enediynes.…”
Section: Introductionmentioning
confidence: 99%
“…Basak et al have subsequently reported that Garratt–Braverman (GB) cyclization depends on the nature of the substituent at the propargyl arm, as well as on the reaction conditions . Another interesting type of cycloaromatization involves a selective gold­(I)-catalyzed rearrangement of aromatic methoxypropynyl acetals, leading to fused catechol ethers . Generally, the usual paradigm for applying electronic effects in organic chemistry is based on the concept that an efficient orbital overlap is required to transmit conjugation and hyperconjugation .…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic addition of carboxylic acids to alkynes is the most straightforward and atom-economical method currently available to obtain enol esters, which are very useful intermediates for organic synthesis [1][2][3][4][5][6][7]. A large number of Groups 8-11 metal complexes able to promote the process have been reported in the literature, predominating those based on ruthenium and gold due to their exquisite regio-and stereo-selectivity [1][2][3][4][5][6][7][8]. In this context, some years ago we disclosed that the bis(allyl)-ruthenium(IV) derivative [RuCl 2 (η 3 :η 3 -C 10 H 16 )(PPh 3 )] (C 10 H 16 = 2,7-dimethylocta-2,6-diene-1,8-diyl; 1) is an excellent catalyst for the selective Markovnikov addition of carboxylic acids to terminal alkynes [9].…”
Section: Introductionmentioning
confidence: 99%